2014
DOI: 10.1371/journal.pone.0110859
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Heat Stress Alters Postnatal Offspring Body Composition Indices and Metabolic Parameters in Pigs

Abstract: The study objectives were to test the hypothesis that heat stress (HS) during gestational development alters postnatal growth, body composition, and biological response to HS conditions in pigs. To investigate this, 14 first parity crossbred gilts were exposed to one of four environmental treatments (TNTN, TNHS, HSTN, or HSHS) during gestation. TNTN and HSHS dams were exposed to thermal neutral (TN, cyclical 18–22°C) or HS conditions (cyclical 28–34°C) during the entire gestation, respectively. Dams assigned t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 44 publications
5
47
1
1
Order By: Relevance
“…No in utero thermal treatment differences were detected in circulating glucose, insulin, NEFA, PUN, and CK ( Table 5). The lack of differences in glucose and NEFA agrees with our previous in utero HS reports (Boddicker et al, 2014), and were not unexpected, as we did not detect gross differences in body composition. However, we previously reported that in utero HS increases future circulating insulin concentration, regardless of postnatal thermal environments (Boddicker et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…No in utero thermal treatment differences were detected in circulating glucose, insulin, NEFA, PUN, and CK ( Table 5). The lack of differences in glucose and NEFA agrees with our previous in utero HS reports (Boddicker et al, 2014), and were not unexpected, as we did not detect gross differences in body composition. However, we previously reported that in utero HS increases future circulating insulin concentration, regardless of postnatal thermal environments (Boddicker et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…The lack of differences in glucose and NEFA agrees with our previous in utero HS reports (Boddicker et al, 2014), and were not unexpected, as we did not detect gross differences in body composition. However, we previously reported that in utero HS increases future circulating insulin concentration, regardless of postnatal thermal environments (Boddicker et al, 2014). Reasons why the current experiment did not corroborate our previous results are not clear, but may be due to infrequent blood sampling in the current study.…”
Section: Discussionsupporting
confidence: 93%
“…One extensively researched experimental model is maternal undernutrition that increases offspring lipid accretion (Ravelli et al, 1976;Barker et al, 1993;Desai et al, 2005;Roseboom et al, 2006). In addition, we recently reported (Boddicker et al, 2014;Johnson et al, 2015b) that in utero HS increases future adipose deposition at the expense of skeletal muscle mass in pigs. Similarities between the in utero undernutrition and HS models, coupled with the fact that HS causes a well-documented reduction in feed intake (FI) in almost all species (Baumgard et al, 2012;Baumgard and Rhoads, 2013;Johnson et al, 2015a), lends itself to the hypothesis that the two in utero insults may be mechanistically linked.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, HS experienced during gestation can result in physiological anomalies that extend into post-gestational life (Shiota and Kayamura, 1989;Chen et al, 2010). In this way, Boddicker et al (2014) suggest that HS during the first half of gestation may have programmed the kits, resulting in an altered postnatal offspring growth and development. In the present study, we demonstrate that kits from does that experienced HS during gestation did not alter postnatal growth until Spanish commercial liveweight (63 d).…”
Section: Discussionmentioning
confidence: 99%